Penguatan Bahasa Inggris bagi Ustaz untuk Mewujudkan Pesantren Bilingual: Program Pengabdian di Pondok Pesantren Darul Falah Mataram - Abrar, Abrar; Arifin, Muhamad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
This community service program aimed to strengthen the English language skills of ustaz at Pondok Pesantren Darul Falah, Mataram City, West Nusa Tenggara, as part of a strategic effort to transform the pesantren into a bilingual institution. The program was conducted over three months (January–March 2024) using a participatory empowerment approach and practical pedagogy, involving 20 ustaz as active partners. The program's stages included a needs analysis through diagnostic tests and interviews, interactive training covering listening, speaking, reading, and writing skills, workshops for developing bilingual teaching materials, microteaching practice sessions with peer feedback, and evaluation through pre-tests, post-tests, and Focus Group Discussions (FGDs). The evaluation results showed a significant increase in the average score from 42.5 to 74.2. The ustaz also reported feeling more confident in using simple English expressions during teaching, and several took the initiative to create bilingual materials. The program had indirect impacts on students, who began to hear and use basic English vocabulary in daily learning contexts. Overall, this program demonstrates that a participatory empowerment model can effectively enhance ustaz’ competencies, foster a collaborative learning culture, and support the development of a bilingual pesantren that remains rooted in Islamic values. Looking ahead, the program is expected to serve as a replicable model for other pesantren and help strengthen their readiness to compete in a globalized era.